A fast massively parallel two-phase flow solver for microfluidic chip simulation. (March 2018) - Kronbichler, Martin; Diagne, Ababacar; Holmgren, Hanna
This work presents a parallel finite element solver of incompressible two-phase flow targeting large-scale simulations of three-dimensional dynamics in high-throughput microfluidic separation devices. The method relies on a conservative level set formulation for representing the fluid-fluid interface and uses adaptive mesh refinement on forests of octrees. An implicit time stepping with efficient block solvers for the incompressible Navier–Stokes equations discretized with Taylor–Hood and augmented Taylor–Hood finite elements is presented. A matrix-free implementation is used that reduces the solution time for the Navier–Stokes system by a factor of approximately three compared to the best matrix-based algorithms. Scalability of the chosen algorithms up to 32, 768 cores and a billion degrees of freedom is shown.